Lifesaving therapeutic plasma exchange by cell saver in an obstetric emergency - vranes, marija s (Medicinski časopis, 2017)
Abnormally high levels of triglycerides (hyperlipidemia) are often the result a number of disorders in the organism, which eventually lead to conditions such as hypothyroidism, nephrotic syndrome, diabetes, biliary tract obstruction, impairment of hepatic function, and others. How to treat extreme hyperlipidemia remains a subject of discussion in medical circles. In this paper, the case of 33-year-old pregnant woman with extreme hyperlipidemia, which is in critical condition were taken to the Clinical Center of Kragujevac, on 31.07.2014. years. After an emergency cesarean section performed, due to the general poor condition of the patient and extremely high levels of triglycerides and cholesterol, is indicated lipofereza, which in our institution is not technically possible, and we had the time strait to find an alternative solution. It was concluded that the apparatus for intraoperative blood salvage can be used successfully not only in heavy bleeding during surgery, but also for cleaning the blood itself, which clearly show the laboratory analysis. Hyperlipidemia, extremely high levels of triglycerides, lipofereza, intraoperative blood salvage, autologous blood transfusion